The Role of Social Media in Increasing Brand Awareness of MSME Products - Lilik Dea Tantri; Mellyana Herawati (Yayasan Meira Visi Persada, 2026)
This study aims to analyze the role of social media in increasing brand awareness of Micro, Small, and Medium Enterprises (MSMEs) products in Indonesia. The research method used a quantitative approach with a survey of 150 MSME owners in Central Java who actively use social media. Data were collected through structured questionnaires and analyzed using descriptive analysis and simple linear regression. The results show that social media usage has a positive effect on increasing MSME brand awareness, with a coefficient of determination of 0.742. Instagram is the most effective platform (78.6%), followed by Facebook (65.3%) and TikTok (43.2%). This research provides practical contributions for MSME actors in utilizing social media as a digital marketing strategy.